Strengthening Management Control System in the Accounting Department: A Study at PT X - Musviyanti; Khairiyani (Proceeding International Conference on Accounting and Finance, 2025)
The implementation of an effective management control system (MCS) is a crucial element in ensuring the efficiency and accuracy of company operations. This study aims to analyze the implementation of MCS in the accounting department of PT X, with a focus on the cultural controls and action controls that have been put in place. A qualitative method was employed, using a case study approach. Data were collected through in-depth interviews with the head of the department and accounting staff to understand the implementation of the MCS. Thematic analysis was used to analyze the data.The findings reveal that although an MCS has been implemented in the accounting department of PT X, its application has not been optimal. Cultural controls, which emphasize the values of thoroughness and compliance, have proven ineffective due to insufficient formal training and inadequate socialization. Meanwhile, action controls, as realized through the implementation of standard operating procedures (SOP), faced challenges such as inconsistencies in interpretation and application among staff, as well as a lack of regular monitoring. Based on these findings, the recommended solutions include strengthening both cultural controls and action controls through more structured training, revising and clarifying SOP for better consistency, enhancing regular monitoring and evaluation mechanisms, and integrating technology systems to improve inter-departmental coordination. This approach is expected to enhance the effectiveness of the MCS in PT X’s accounting department while contributing to the company’s overall efficiency and performance.